A aprendizagem do educador: estratégias para a construção de uma didática on-line - Bruno, Adriana Rocha (2007)
The current thesis intends to develop an investigation on adult learning, specifically the one that concerns the educator, and to search for didactic strategies that can assist the development of this process within on-line education environments. The qualitative research, subsidized by the theory of Experiential Learning and by the dimensions studied in the field of Didacticism through systemic reflection and practice, was developed from the method of content analyses, having the following as its instruments: documents made available through an educator s development course, via online education, and via contents co-developed through interviews with teachers, students and one of the coordinators to the course investigated. The studies developed show that the adult learns with effect from experiences developed through cycles, within an upward spiral, throughout their lives. These cycles are experienced starting from the concept of convergent plasticity to organic working, from social integration, and from individual development built by biopsycho- socio aspects. The plasticity is the base element for the human organism due to its adaptability, suitability and transformation, and all the elements related to human learning have to be coherent with such premise. The online learning environments used for the development of educators should, within didactic strategies, see We tried, in the light of the data interpreted and the theories studied, to propose teaching strategies for the construction of an online Didacticism that can favor the educator s apprenticeship